2001
DOI: 10.1016/s0893-133x(00)00222-0
|View full text |Cite
|
Sign up to set email alerts
|

Altered HPA Axis Responsivity to Metyrapone Testing in Methadone Maintained Former Heroin Addicts with Ongoing Cocaine Addiction

Abstract: Metyrapone testing, a provocation of hypothalamicpituitary-adrenocortical (HPA) axis function, was performed in 39 in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(44 citation statements)
references
References 33 publications
(20 reference statements)
1
41
0
1
Order By: Relevance
“…Of particular interest, AVP gene expression that increased by protracted cocaine withdrawal was insensitive to opioid receptor blockade, since we observed no effect of naloxone on AVP mRNA levels during cocaine withdrawal, which suggests less inhibition of AVP neurons by endogenous opioids in cocaine-withdrawn rats. Studies in human cocaine addicts found a decreased opioid activity (m opioid receptor-preferring component) in the control of the HPA axis (Schluger et al, 2001;Koob and Kreek, 2007), supporting this relative endogenous opioid-deficiency hypothesis. Although the naloxone dose in the present study was relatively low and preferential for the m opioid receptor, we cannot at this point exclude the involvement of other opioid receptors, such as k opioid receptors.…”
Section: Interaction Between Ppvn Avp and Opioid Receptorsmentioning
confidence: 78%
“…Of particular interest, AVP gene expression that increased by protracted cocaine withdrawal was insensitive to opioid receptor blockade, since we observed no effect of naloxone on AVP mRNA levels during cocaine withdrawal, which suggests less inhibition of AVP neurons by endogenous opioids in cocaine-withdrawn rats. Studies in human cocaine addicts found a decreased opioid activity (m opioid receptor-preferring component) in the control of the HPA axis (Schluger et al, 2001;Koob and Kreek, 2007), supporting this relative endogenous opioid-deficiency hypothesis. Although the naloxone dose in the present study was relatively low and preferential for the m opioid receptor, we cannot at this point exclude the involvement of other opioid receptors, such as k opioid receptors.…”
Section: Interaction Between Ppvn Avp and Opioid Receptorsmentioning
confidence: 78%
“…Similarly, responses to other probes of HPA axis function, such as ACTH infusion or metyrapone (an oral 11-b-hydroxylase inhibitor that blocks the final step in cortisol synthesis in the adrenal glands) testing have been found to be within normal limits in stabilized methadone-maintained subjects (Kreek, 1972(Kreek, , 1973aCushman Jr and Kreek, 1974;Kreek et al, 1984). In recent studies, we have also shown normal HPA response to metyrapone in stable-dose methadone-maintained subjects but not in methadone-maintained subjects with ongoing cocaine dependence (Schluger et al, 2001).…”
Section: Introductionmentioning
confidence: 77%
“…Positron emission tomography (PET) studies performed in stable-dose methadone-maintained subjects have shown that only 19-32% of m-opiate receptors are occupied during steady-state methadone therapy thereby allowing the remaining receptors to function in their normal physiologic capacity modulating pain and analgesia, immune function, and the HPA axis (Kling et al, 2000). The return of normal HPA axis responsivity during stable-dose methadone maintenance is likely due to this and, in part, to the normalization of opioidergic tone evidenced by the normalization of HPA responsivity to the removal of the other, and major, modulator of HPA axis response, glucocorticoid negative feedback, using metyrapone (an inhibitor of cortisol synthesis) (Kreek, 1972(Kreek, , 1973aKreek et al, 1984;Kennedy et al, 1990;Schluger et al, 2001). Further supporting the hypothesis of normalized opioidergic tone in methadone maintenance, former heroin addicts in long- term abstinence without methadone pharmacotherapy have increased HPA responsivity to metyrapone testing (Kreek et al, 1984).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We assessed plasma adrenocorticotropic hormone (ACTH) and corticosterone (CORT) because they are known to be altered by chronic exposure to opiates and cocaine (Schluger et al, 2001;Zhou et al, 1999Zhou et al, , 2003. Finally, because glucocorticoids exert a negative feedback control on the release of ACTH and beta-endorphins by the anterior pituitary, we quantified mRNA expression of their precursor (POMC) in this region.…”
Section: Introductionmentioning
confidence: 99%